Rekonstruksi Hukum Poligami Tidak Tercatat di Indonesia: Model Pengakuan Bersyarat sebagai Jalan Tengah Keadilan Keluarga - Muhammad Akmal Apriliansyah (Pro Justicia: Jurnal Hukum dan Sosial, 2026)
The practice of unregistered polygamy in Indonesia continues to escalate, leaving a legal vacuum that has systemic impacts on the vulnerability of wives and children. This phenomenon is often justified through a reductionist understanding of religious texts to bypass the rigidity of judicial bureaucracy. This study aims to analyze the disparity between formal regulations and the sociological reality of polygamy, as well as to formulate a just legal policy. Employing a qualitative approach with the analytical framework of maqashid al-shariah (the fundamental objectives of Islamic law), this study deconstructs the meaning of justice in polygamy by strictly separating the capacity to fulfill material rights from human affective limitations. The results confirm that the absence of polygamy legality perpetuates gender relational inequality and triggers structural poverty due to the loss of children's civil status. To bridge the discursive polarization between abolitionists demanding total criminalization and permissive groups, this research formulates a "Conditional Recognition Model" as an alternative solution. This model integrates three policy pillars: the certainty of children's civil rights through biological evidence, the application of deterrent sanctions for perpetrators, and the measured obligation of marriage legalization (isbat nikah). In conclusion, policy reconstruction through this model is able to harmonize legal certainty with substantive justice, thereby ensuring equality and the protection of fundamental human rights within the Islamic family law system in Indonesia.